Application of Ultrasound Guided Air Enema Reduction in the Treatment of Intussusception at the Lao National Children’s Hospital - Souliphone, Vongphet; SOULITHONE, Vongphet; SONNASINH, Phetdavanh; Liyevu, Lifusue; Sihalath, Kongthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objective of research was to study the effectiveness of treating intussusception by pneumatic reduction enema using ultrasound guidance. A retrospective data study conducted over a period of 1 year and 3 months, from April 2021 to July 2022, focusing on cases of intussusception in a children's hospital. The sample consisted of 35 patients, selected using a random sampling method based on clinical symptoms and ultrasound findings indicative of intussusception. This study included cases where the duration of symptoms did not exceed 48 hours. All cases underwent pneumatic reduction enemas guided by ultrasound. Cases with signs of peritonitis, severe dehydration, or clinical symptoms lasting longer than 48 hours were excluded from the study. The Result found that: Pneumatic intussusception reduction was successful in 31 patients (overall success rate 88.50%) followed by auscultation. Only 4 patients (11.42%) required surgical intervention due to unsuccessful pneumatic reduction. In our study, the 4 cases treated surgically involved manually reducing the intussusception without bowel resection. Within 3 months after successful pneumatic reduction, only 2 patients (5.71%) recurred. We found that the technique of transrectal air reduction in the treatment of Intussusception in children, monitored by ultrasound, is easy to use and highly effective. The treatment has no complication, is convenient and safe, the success rate in our study is 88.57 % with a recurrence rate of 5.71% with no intestinal perforate during the procedure. It can prevent and reduce the need for surgical intervention in patients presenting with early symptoms and in patients without signs of peritonitis. We recommend this technique of transrectal air pressure reduction for treating intussusception be implemented in provincial and district hospitals throughout Laos.